O Brasil em traduções francesas: um estudo dos paratextos de antologias contemporâneas de contos - Coutinho, Janaína Araújo (2016)
This dissertation has as its objective to analyze paratexts and accompanying discourses found in contemporary anthologies of Brazilian tales translated to French. Considering that the information found in these materials contribute to reinforce the images already existent or to compose new images of a country and its culture, we tried to find which Brazil is being exposed to the francophone readership through the narratives. The theoretical background on paratexts is based on the contributions of Gérard Genette (Paratextos Editoriais, 2009) and the following studies in the scope of Translation Studies, promoted mainly by Teresa Dias Carneiro (2014) and Marie-Hélène C. Torres (2004). To the study of images, we used Celeste H. M. R. de Sousa’s works (especially Introdução à Imagologia, 2004) which discuss the relevance of the image, of the formed representativeness of a culture and a country through literature. We selected the study of the anthologies Contes de Noël brésiliens (1997), Fleur, téléphone et jeune fille… et autres contes brésiliens (1980), Des nouvelles du Brésil (1998), Je suis favela (2011) and Je suis toujours favela (2014) because we understand that the translation of these kind of narratives increases the possibility of representation of an author, textual gender or culture towards the Other and its imaginary.